2014
DOI: 10.1101/gr.168963.113
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding origins of anthropoid traits and a new null model of transposon functionalization

Abstract: Little is known about novel genetic elements that drove the emergence of anthropoid primates. We exploited the sequencing of the marmoset genome to identify 23,849 anthropoid-specific constrained (ASC) regions and confirmed their robust functional signatures. Of the ASC base pairs, 99.7% were noncoding, suggesting that novel anthropoid functional elements were overwhelmingly cis-regulatory. ASCs were highly enriched in loci associated with fetal brain development, motor coordination, neurotransmission, and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…ERVs are a major source of genetic innovation and can generate primate-specific regulatory sites that act as enhancers or transcription start sites of nearby genes (del Rosario et al, 2014;Faulkner et al, 2009;Feschotte and Gilbert, 2012;Jacques et al, 2013;Kunarso et al, 2010;Rebollo et al, 2012). Here, we show that the regulatory elements of ERVs systematically control their own stage-specific expression in human embryos.…”
Section: Discussionmentioning
confidence: 90%
“…ERVs are a major source of genetic innovation and can generate primate-specific regulatory sites that act as enhancers or transcription start sites of nearby genes (del Rosario et al, 2014;Faulkner et al, 2009;Feschotte and Gilbert, 2012;Jacques et al, 2013;Kunarso et al, 2010;Rebollo et al, 2012). Here, we show that the regulatory elements of ERVs systematically control their own stage-specific expression in human embryos.…”
Section: Discussionmentioning
confidence: 90%
“…The LacZ reporter clones were constructed as previously described (del Rosario et al 2014). PCR fragments corresponding to tested regions were cloned into the pENTR plasmid (Invitrogen) and transferred into the Gateway-compatible hsp68-LacZ reporter vector using LR recombination.…”
Section: Lacz In Embryonic Mousementioning
confidence: 99%
“…Although previous studies have suggested a role for transposable elements (TEs) in the evolution of gene regulation, validating the functional contribution of TEs in mammalian gene regulation remains a challenge (McClintock 1950(McClintock , 1984Britten and Davidson 1969;Davidson and Britten 1979;Jordan et al 2003;Bejerano et al 2006;Wang et al 2007;Bourque et al 2008;Sasaki et al 2008;Markljung et al 2009;Kunarso et al 2010;Lynch et al 2011Lynch et al , 2015Schmidt et al 2012;Chuong et al 2013Chuong et al , 2016Jacques et al 2013;Xie et al 2013;del Rosario et al 2014;Sundaram et al 2014;Du et al 2016;Rayan et al 2016;Ward et al 2017).…”
mentioning
confidence: 99%